Status Epilepticus Manifested as Continuous Epileptic Spasms - Liao, Jianxiang; Huang, Tieshuan; Srour, Myriam; Xiao, Yuhan; Chen, Yan; Lin, Sufang; Chen, Li; Hu, Yan; Men, Lina; Wen, Jialun; Li, Bing; Wen, Feiqiu; et al. (Frontiers in Neurology, 2020)
Objective: The etiology and outcome of status epilepticus with continuous epileptic spasms have not been fully understood; and only rare cases have been reported in the literature. Here, we described 11 children, who manifested continuous epileptic spasms with various etiologies and different outcomes. Methods: This is a case series study designed to systematically review the charts, video-electroencephalography (video-EEG), magnetic resonance images, and longitudinal follow-up of patients who presented continuous epileptic spasms lasting more than 30 min. Results: Median age at onset was 2 years old, ranging from 2 months to 5.6 years. The etiology of continuous epileptic spasms for these 11 cases consisted of not only some known electro-clinical epilepsy syndromes like West Syndrome and Ohtahara Syndrome, but also secondary symptomatic continuous epileptic spasms, caused by acute encephalitis or encephalopathy, which extends the etiological spectrum of continuous epileptic spasms. The most characteristic feature of these 11 cases was prolonged epileptic spasms, lasting for a median of 13.00 days (95% CI: 7.26–128.22 days). The interictal EEG findings typically manifested as hypsarrhythmia or its variants, including burst suppression. Hospital stays were much longer in acute symptomatic cases than in primary epileptic syndromic cases (59.67 ± 50.82 vs. 15.00 ± 1.41 days). However, the long-term outcomes were extremely poor in the patients with defined electro-clinical epilepsy syndromes, including severe motor and intellectual developmental deficits (follow-up of 4.94 ± 1.56 years), despite early diagnosis and treatment. Continuous epileptic spasms were refractory to corticosteroids, immuno-modulation or immunosuppressive therapies, and ketogenic diet. Conclusion: Continuous epileptic spasms were associated with severe brain impairments in patients with electro-clinical syndromes; and required long hospital stays in patients with acute symptomatic causes. We suggest to include continuous epileptic spasms in the international classification of status epilepticus, as a special form. Further investigations are required to better recognize this condition, better understand the etiology, as well as to explore more effective treatments to improve outcomes.